Localized accumulation of kappa restricted Russell body‐containing plasma cells in tonsil - Vazmitsel, Maryna A. (Clin Case Rep, 2019)
An abnormal clonal plasma cell proliferation with Russell bodies is rare in chronic inflammatory reactions in adult patients. We describe the first case of light chain restricted Russell body accumulation within germinal centers of lymphoid follicles of the tonsil in a child. This should not be confused with a neoplastic process.